2018
DOI: 10.1021/acs.molpharmaceut.8b00537
|View full text |Cite
|
Sign up to set email alerts
|

Boosted Memory and Improved Brain Bioavailability of Rivastigmine: Targeting Effort to the Brain Using Covalently Tethered Lower Generation PAMAM Dendrimers with Lactoferrin

Abstract: Currently, there is no treatment strategy which can reverse the process of neuro-degeneration in progression of Alzheimer's disease (AD). Practically, it is desired to achieve and maintain high therapeutic doses in the brain, but it is hard due to selective permeability of the blood-brain barrier (BBB). In the present study, lactoferrin (Lf) was conjugated to polyamidoamine generation 3.0 (PAMAM G3.0) dendrimers for the effective delivery of rivastigmine (RIV) to the brain. Conjugation of PAMAM G3.0 with lacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Conclusively, as per the results, it could be conveyed that Lf was able to deliver RIV to the brain in higher concentrations using the PAMAM-Lf conjugate and this approach was safer. Lactoferrin is a protein responsible for the transportation of iron across the BBB via brain ligand–receptor-based mechanism …”
Section: Introductionmentioning
confidence: 99%
“…Conclusively, as per the results, it could be conveyed that Lf was able to deliver RIV to the brain in higher concentrations using the PAMAM-Lf conjugate and this approach was safer. Lactoferrin is a protein responsible for the transportation of iron across the BBB via brain ligand–receptor-based mechanism …”
Section: Introductionmentioning
confidence: 99%
“…In fact, when compared with transferrin (Tf) [215,216] and OX-26 (a Tf receptor antibody) [215] Lf displayed higher brain uptake. Accordingly, different types of Lf-funtionalized nanoparticles carrying therapeutic molecules have been tested in animal models of PD [217][218][219] and AD [220,221] showing improved therapeutic outcomes.…”
Section: Aging-related Ndds-ad and Pdmentioning
confidence: 99%
“…It also shows significant improvement in locomotor activity and memory of the rat brain. 113 Li and coworkers (2012) developed a fourth generation, transferrin modified PAMAM dendrimers for brain delivery of tamoxifen. The study demonstrated considerably higher drug loading and enhanced BBB permeation.…”
Section: Dendrimersmentioning
confidence: 99%